Antibacterial and Antioxidant activities of Indonesian ginger (jahe emprit) essential oil extracted by hydrodistillation - Nurul Azizah; Euis Filaila; Salahuddin Salahuddin; Egi Agustian; Anny Sulaswatty; Nina Artanti (Research Center for Chemistry - LIPI, 2018)
The rhizome of ginger is commonly used as a spice, food, beverage as well as medicine. Plant essential oils including from ginger have been widely used for food preservation, pharmaceutical and alternative medicines. Currently there are growing interest of consumer for natural sources such as essential oils for natural antibacterial and antioxidant. Jahe emprit (Zingiber officinale var. Amarum) is one of Indonesian ginger variety used to obtain ginger essential oil. The objective of current study was to investigate the effect of solvent to feed (SF) ratio in hydrodistillation process on yield, chemicals content, antibacterial and antioxidant activities of ginger essential oils from jahe emprit. SF ratio used in this study is 0.7: 1, 1.7: 1, 2.7: 1. Chemicals content was conducted using GCMS analysis. Antibacterial assay was conducted using disc diffusion method against Escherichia coli and Staphylococcus aureus. Antioxidant assay was conducted using DPPH free radical scavenging assay. The results show that the highest essential oil yield was obtained from SF ratio 1.7:1 which gave yield of 3.7%. GCMS analysis shows that camphene was always the major compound present in those 3 SF ratio, although the amount present was differed. Besides, 4 other major compounds present were varied. Antibacterial assay using 1% concentration showed ginger oil obtained from SF 0.7:1 and 2.7:1 have the same activities for S. aureus, whereas SF ratio 1.7:1 has the lowest activities. However for E. coli, all SF ratio gave same results. For antioxidant activities at 1000 ppm concentration, the highest activity was obtained from SF ratio 2.7:1